Efficacy of Neem {Azadirachta indica) and Pineapple {Ananas comosus) Leaf Powder on Ascaridia galli Infection in Chicken - Kumar, Anand; Sinha, Sucheta; Kumari, Savita; Kumari, Sudha; Sinha, SRP; Kumar, Pankaj (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A study was conducted to assess the efficacy of herbs Azadiracta indica (Neem) and Ananus  comosus (Pineapple) for the control of ascaridiosis in chicken. Neem leaf powder (@100 mg /kg  feed /day), Pineapple leaf powder (1 gm /kg feed /day) and combined preparation (100 mg + 1 gm  /kg feed/day) were found effective against Ascaridiagalli. The percent efficacy by declining rate of  EPG and worm count revealed that combined preparation of Neem and Pineapple leaf powder was  most effective, followed by Pineapple leaf powder and Neem leaf powder at 28 day post treatment.  The present study revealed that Neem and Pineapple could be safe and effective dewormer and  may provide an alternative of chemical anthelmintics.
Keywords: Neem; Pineapple; anthelmintics; chickens; Ascaridiagalli